Characterization of two reductases MaLAR and MaANR revealed their roles in proanthocyanidin biosynthesis in mulberry - Feng, Zhiheng; Li, Peijun; Yang, Guang; Wang, Yining; Li, Mengqi; Wu, Jiangting; Chao, Nan; Liu, Li (Frontiers in Plant Science, 2026)
Proanthocyanidins (PAs), polymers of flavan-3-ols, are crucial for the sensory quality and stress defense of mulberry (Morus spp.). The biosynthesis of their monomers, catechin and epicatechin, are catalyzed by leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR), respectively, representing key rate-limiting steps that determine PA composition and abundance. In this study, systematic functional analyses including phylogenetic analysis, quantified spatio-temporal expression profiles during fruit development (S1-S4 stages), in vitro enzymatic assay, knock-down using Virus-Induced Gene Silencing (VIGS) in mulberry leaves and heterologous overexpression in Arabidopsis thaliana were conducted to reveal their roles in proanthocyanidin biosynthesis in mulberry. Results showed that MaLAR (969 bp) and MaANR (1014 bp) were successfully cloned and phylogenetically conserved. Spatio-temporal expression analysis revealed distinct patterns: MaLAR expression continuously increased, reaching highest expression level at the fully ripe stage (S4), whereas MaANR showed highest expression level at the color-turning stage (S2). In vitro enzymatic assays confirmed that MaLAR catalyzed the formation of catechin from leucoanthocyanidin, and MaANR catalyzed the formation of epicatechin from anthocyanidin. VIGS-mediated silencing of either gene in mulberry leaves led to significant reduction in total PA content. Conversely, heterologous overexpression of MaLAR or MaANR in Arabidopsis resulted in significant increase of PA in the seed coat. Our findings confirm that MaLAR and MaANR are conserved, key positive regulators of PA biosynthesis in mulberry. The differential expression patterns during fruit ripening suggest they play distinct, temporally regulated roles in determining the final PA composition and content. These results provide an important theoretical basis and represent important targets for the metabolic engineering and molecular breeding of mulberry for improved fruit quality.